Pengaruh Penerapan Sistem Informasi Manajemen Daerah (SIMDA) Keuangan Terhadap Pengelolaan Keuangan Daerah Pemerintah Kabupaten Ogan Ilir - Masnoni; Lia Sari; Irsan; Roy Saleh; Hilwa Anggraini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The formulation of the problem in this study is how the implementation of the Financial Regional Managemen Information System (SIMDA) affects the regional financial managemen of the Government of Oga Ilir Regency. The purpose of this study was to determine the effect of impemeting a financial regional managemen informatioan system (SIMDA) on tge regional financial management of the OgAN iLir Government. The type of resersch esed in this study is desctiptive quantitative namely the analysis carried out in data in the form of numbers to apply an explanation of these number. The sample in this study was a saturated sample of 76 people consisting of the head of the OPD and the treasure within the Ogan Ilir Regency Government. The data collection technique used in this study was by way of direct interviews and quetionnasires. Based on the result of the study, there is a significant effect of the implementation of The Regional Managemet Information System (SIMDA) on financial management of the regional financial management of the Ogan Ilir Regional Government, Where it is know that e result of the hypothetical test now that the calculated t value for tge regional management information system variable (x) is 5.310 whilw the t table with significant level (α) of 0.05 (5%) and df=n-k-1 (76-1-1) 74 is 1.665. So, it can be concluded that H0 is reject and Ha is accepted and reject by H0 and the significant value x 0.002 is smeller than 0.005. So, it was concluded the regional managemen information system significantly affects financial quality.